Nuclear Imaging of Glucose Transport/Metabolism – An Interesting Tool to Screen Insulin Resistance, Refine Diagnosis of Type 2 Diabetes, Understand Disease Mechanisms, and/or Evaluate New Therapies - Perret, P.; Henri, M.; Slimani, L.; D.Fagret; Ghezzi, C. (IntechOpen, 2011)
None